Desenvolvimento e otimização de sistema eletroquímico assistido por micro-ondas - Ribeiro Neto, João Francisco Ramos (Universidade Federal de São Carlos, 2025)
In this work, the assembly of an electrochemical system coupled to a conventional microwave oven was optimized to investigate its feasibility for reproducible microwave-assisted electrochemistry. The study addressed the influence of the main system variables, such as the height of the electrode inside the microwave cavity, the electrolyte concentration, and the solution temperature, on the variation of the open-circuit potential during 7 s microwave pulses. The cleanliness of the system components was verified by cyclic voltammetry, and the solution resistance was evaluated by EIS. Several tools were specifically developed for this system, including custom-machined Teflon flow tubes and a laser positioner with magnetic mounting. The experiments performed using a 23 factorial design were successful mainly due to the reduction of the microwave oven’s input voltage, which prevented electrical arcing that previously damaged the system. The results showed that electrode height and electrolyte concentration are significant factors in the electrochemical response, contributing to a localized increase in temperature at the electrode surface. Comparison with computational simulations confirmed the validity of the experimentally observed trends, aligning with previous findings and demonstrating the effectiveness of the system in providing localized thermal assistance during electrochemical experiments. This study opens new possibilities for the application of microwaves in electrochemistry, presenting a simpler and more reproducible assembly method compared with those previously described in the literature.
Development and optimization of a microwave-assisted electrochemical system
Keywords: Sistema eletroquímico; Micro-ondas; Potencial de circuito aberto; Planejamento fatorial; Aquecimento localizado; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::ELETROQUIMICA; 9. Indústria, Inovação e Infraestrutura